Enhancement of docosahexaenoic acid production by low-energy ion implantation coupled with screening method based on Sudan black B staining in Schizochytrium sp. (December 2016) - Fu, Jie; Chen, Tao; Lu, Hao; Lin, Yuanfeng; Xie, Xinlei; Tian, Hua; Zheng, Cao; He, Dongping
Highlights: Low-energy ion implantation was applied to induce high-DHA producing mutants. Sudan black B staining method was modified for selection of targeted mutants. The maximum DHA yield of mutant strain S1 was 6.52 g/L under optimum conditions. The percentage of DHA in total lipid of S1 was 46.2% under optimum conditions. Abstract: Schizochytrium sp. is a hopeful docosahexaenoic acid (DHA) producing candidate due to its rapid growth rate and high DHA proportion in total lipid content. In this study, low-energy ion implantation was applied to Schizochytrium sp. to induce high DHA-producing mutants. Screening these mutants by Sudan black B staining, a mutant strain S1 which showed a 61% improvement in DHA production than that of the parent strain was successfully selected. Subsequently, parameters of DHA production of mutant strain S1 were optimized in a 500-mL Erlenmeyer flask. Under the optimum fermentation conditions, the production of DHA and the percentage of DHA in total lipid of mutant strain S1 were 6.52 g/L and 46.2%, respectively. This study provides an effective breeding strategy for improved DHA production of Schizochytrium sp. through combination of the novel mutagenesis technology, the effective screening method and fermentation optimization.